2014
DOI: 10.1371/journal.pone.0107516
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Deprivation Therapy for Prostate Cancer Is Associated with Cardiovascular Morbidity and Mortality: A Meta-Analysis of Population-Based Observational Studies

Abstract: BackgroundThere is no consensus regarding whether androgen deprivation therapy (ADT) is associated with cardiovascular disease (CVD) and cardiovascular mortality (CVM). The objective of this study was to determine the role of ADT for prostate cancer (PCa) in development of cardiovascular events (CVD and CVM).Methods and FindingsWe performed a meta-analysis from population-based observational studies comparing ADT vs control aimed at treating PCa in patients with PCa, reporting either CVD or CVM as outcome. Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 43 publications
2
86
1
2
Order By: Relevance
“…[9][10][11] In our study, we observed that supervised regular exercise training decreased inflammation, reduced car diovascular risk, and improved functional status in men with high grade PCa during ADT with RT. The exercise program prescribed (duration, fre quency, and intensity) was designed in accordance with the American Cancer Society recommen dations for cancer patients.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…[9][10][11] In our study, we observed that supervised regular exercise training decreased inflammation, reduced car diovascular risk, and improved functional status in men with high grade PCa during ADT with RT. The exercise program prescribed (duration, fre quency, and intensity) was designed in accordance with the American Cancer Society recommen dations for cancer patients.…”
mentioning
confidence: 85%
“…recurrence. 10,11 It has been well documented that the incidence of cardiovascular events is signif icantly higher for individuals who smoke, have diabetes, hypertension, chronic pulmonary ob struction, high body mass index (BMI), high lev els of triglycerides (TGs) and creatinine, and low levels of high density lipoprotein (HDL) choles terol. However, even among study participants without these traditional risk factors, elevated lev els of inflammatory markers (interleukin [IL]1β, IL 6, tumor necrosis factor α [TNF α]) prove to be the best predictors for coronary heart disease and congestive heart failure.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…[9][10][11][12][13] Although the literature investigating this association is still controversial secondary to differences in study design, outcomes, and at-risk populations studied, several meta-analyses of observational studies have suggested a link between ADT and CV disease and mortality. 14,15 This increased risk of CV events has been observed largely during the first year after initiation of testosterone therapy. [11][12][13] There have been several proposed mechanisms explaining these more acute physiological changes as compared to the development of metabolic syndrome with prolonged ADT use.…”
Section: Introductionmentioning
confidence: 99%
“…6 Additional analyses using the SEER database, 19 Danish Cancer Registry, 20 and Swedish PcBaSE 21 have corroborated this data, yet others have found no clear association between use of gonadotropin-releasing hormone agonists and CE risk. 22 Meta-analyses have been conducted to reconcile this data, 23,24 but fundamental weaknesses of observational studies limit interpretation. For instance, while observational studies provide large patient cohorts for study, they are particularly susceptible to bias from inconsistent ICD-9 coding and inconsistent or limited patient follow-up.…”
Section: Discussionmentioning
confidence: 99%